On the Cauchy-problem for generalized Kadomtsev-Petviashvili-II equations - Axel Gruenrock (Electronic Journal of Differential Equations, 2009)
The Cauchy-problem for the generalized Kadomtsev-Petviashvili-II equation $$ u_t + u_{xxx} + partial_x^{-1}u_{yy}= (u^l)_x, quad l ge 3, $$ is shown to be locally well-posed in almost critical anisotropic Sobolev spaces. The proof combines local smoothing and maximal function estimates as well as bilinear refinements of Strichartz type inequalities via multilinear interpolation in $X_{s,b}$-spaces.